A Six-Year strategic financial plan for Lorenzo Shipping Corporation - Baldevia, Bernadette A., Dela Paz, Irish S., Mabunga, Twainy Grace T., Polintan, Pamela Marie A., Tayag, Jaira Jane C 4 0 16; 5
Executive Summary: Lorenzo Shipping Corporation (LSC) faces pressing financial and operational challenges that threaten its stability and competitiveness in the shipping industry. Key issues include rising direct costs such as terminal fees and service costs, a heavy reliance on borrowed funds that increase financial obligations, and delays in customer payments that constrain cash flow. These factors have collectively eroded profit margins, hindered financial sustainability, and limited operational efficiency. This paper presents a strategic framework to address these challenges, focusing on operational cost optimization and improved cash flow management. The proposed solutions include implementing a Fleet Modernization and Maintenance Optimization strategy to reduce direct costs and enhance efficiency. This involves upgrading LSC's fleet with fuel-efficient vessels, introducing predictive maintenance technologies, and optimizing maintenance operations to reduce downtime and extend vessel lifespans. Concurrently, stricter payment collection policies will be enforced to accelerate cash inflows, while debt reduction initiatives will minimize financial risks and free up resources for reinvestment in core business areas. The strategy also emphasizes sustainability by exploring green financing and other cost-effective funding options to support fleet upgrades and operational improvements. By leveraging these initiatives, LSC can achieve significant cost reductions, improve service reliability, and strengthen its financial foundation. With this integrated approach, LSC aims to rebuild its financial health, regain operational stability, and enhance its position as a resilient and competitive player in the shipping industry. The proposed plan aligns with long-term goals of profitability and sustainability while maintaining the quality and reliability of its services.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2